2023 Fitness Trends from Around the Globe. (January 2023) - Kercher, Vanessa M. (Martinez); Kercher, Kyle; Levy, Paul; Bennion, Trevor; Alexander, Chris; Amaral, Paulo Costa; Batrakoulis, Alexios; Chávez, Lino Francisco Jacobo Gómez; Cortés-Almanzar, Paola; Haro, Jorge López; Zavalza, Adrián Ricardo Pelayo; Rodríguez, Luis Eduardo Aguirre; et al.
Apply It!: From this article, the reader should be able to: Identify top 20 fitness trends for Australia, Brazil, Europe, Mexico, Portugal, Spain, and the United States. Recognize individual and unique fitness trends represented within the seven aforementioned regions. Identify top five trends for each region during the last 3 years.